Therapist's guide to learning and attention disorders - Fine, Aubrey H.; Kotkin, Ronald A. (Practical resources for the mental health professional., 2003)
Practitioners seeking the most current advances in the field of ADHD and LD must often bridge the gap between research and practice. The Therapist's Guide to Learning and Attention Disorders provides that bridge through the authors, who are both researchers and practitioners with extensive experience in providing direct services to children and adults with ADHD and LD. Practitioners are often faced with the choice of reading research or consulting text that suggest strategies or techniques for serving children and adults with ADHD that are not base on research. This book provides practitioners a translation of research to practice in one source. This book provides practical forms, illustrations, and rating scales that can be readily incorporated into practice. The last chapter takes a fascinating look into the role of various practitioners twenty years into the future. * Contains innovative strategies for assessment of ADHD and LD * Provides practical and useful illustrations, forms, and rating scales for use in practice * Provides discussions of future practice and developments in the field of ADHD and LD * Presents case studies illustrating best practices.